2003
DOI: 10.1074/jbc.m302630200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Disease-associated Keratin 16 Gene Expression by Epidermal Growth Factor Is Regulated through Cooperation of Transcription Factors Sp1 and c-Jun

Abstract: Overexpression of keratin 16 has been observed in keratinocytes in those skin diseases characterized by hyperproliferation such as psoriasis. Therefore, keratin 16 is usually referred to as a disease-associated keratin. In the present study, we found that epidermal growth factor (EGF) increased the expression of keratin 16 mRNA and protein synthesis in a time-dependent manner in HaCaT cells. Reporter assays revealed that the EGF response region was in the range of ؊162 to ؊114 bp. Disruption of the Sp1 site (؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…Since both the C/EBP and Sp1 binding sites on the gene promoter are required for the LPS-induced gene expression of IL-10 in mouse macrophage cells [45], our present results indicate that C/EBPd acts on both the C/EBP and Sp1 binding sites on the gene promoter of IL-10 to activate the gene transcription. A transcription factor acting through its own response element and also through its interaction with Sp1, followed by the binding of the latter formed complex to the Sp1 response element on a gene promoter was also observed in our previous study examining the functional role of c-Jun and Sp1 in epidermal growth factor (EGF)-induced gene activation of disease-associated keratin 16 in human keratinocytes [48]. In the study of keratin 16 gene expression, we found that both AP1 and Sp1 binding elements on the gene promoter are required for the EGF-induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Since both the C/EBP and Sp1 binding sites on the gene promoter are required for the LPS-induced gene expression of IL-10 in mouse macrophage cells [45], our present results indicate that C/EBPd acts on both the C/EBP and Sp1 binding sites on the gene promoter of IL-10 to activate the gene transcription. A transcription factor acting through its own response element and also through its interaction with Sp1, followed by the binding of the latter formed complex to the Sp1 response element on a gene promoter was also observed in our previous study examining the functional role of c-Jun and Sp1 in epidermal growth factor (EGF)-induced gene activation of disease-associated keratin 16 in human keratinocytes [48]. In the study of keratin 16 gene expression, we found that both AP1 and Sp1 binding elements on the gene promoter are required for the EGF-induced gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have provided a proposed model for the transcriptional regulation of the keratin 16 gene, indicating that Sp1 recruits c-Jun to the promoter through the binding of Sp1 to the Sp1 site and coactivators p300/CBP interact with Sp1 and AP1 proteins and participate in the transcriptional regulation for EGF induction of keratin 16 gene expression in keratinocytes (Wang and Chang, 2003). The aim of the present work is to further investigate the signaling pathway and the regulatory mechanism of these nuclear factors involved in the transcriptional control of keratin 16 upon EGF treatment.…”
mentioning
confidence: 99%
“…Keratinocytes in wound sites and psoriatic lesions are also similarly differentiated; both express keratin 6 (K6), keratin 16 (K16) and keratin 17 (K17) instead of the standard keratin 1 (K1) and keratin 10 (K10) expressed by normal differentiating suprabasal keratinocytes (de Jong et al, 1991;Mommers et al, 2000;Wang & Chang, 2003). This suggests that transcriptional regulation responsible for both wound healing and psoriasis are similar.…”
Section: Events In Woundingmentioning
confidence: 77%